2021
DOI: 10.1007/s10484-021-09528-w
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Cardiac Chronotropic Control: Implications for Heart Rate Variability Research

Abstract: There is a continuing debate concerning “adjustments” to heart period variability [i.e., heart rate variability (HRV)] for the heart period [i.e., increases inter-beat-intervals (IBI)]. To date, such arguments have not seriously considered the impact a demographic variable, such as gender, can have on the association between HRV and the heart period. A prior meta-analysis showed women to have greater HRV compared to men despite having shorter IBI and higher heart rate (HR). Thus, it is plausible that men and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 24 publications
(41 reference statements)
8
30
1
Order By: Relevance
“…Our second hypothesis that relations between HRV and COVID-19-associated worries would be more pronounced in women compared to men was supported, emphasizing the previously suggested importance of considering sex with respect to both HRV ( Williams et al, 2022 ) and worry tendency ( Robichaud et al, 2003 ).…”
Section: Discussionsupporting
confidence: 54%
“…Our second hypothesis that relations between HRV and COVID-19-associated worries would be more pronounced in women compared to men was supported, emphasizing the previously suggested importance of considering sex with respect to both HRV ( Williams et al, 2022 ) and worry tendency ( Robichaud et al, 2003 ).…”
Section: Discussionsupporting
confidence: 54%
“…Yet, higher psychopathology (i.e., depression and anxiety) is associated with greater substance issues (36,37), and thus, ER difficulties may be particularly linked with a history of drug use in women. Relatedly, studies have shown that the negative association between resting HRV and both self-reported ER difficulties (27) and HR (38) is stronger in women than men; these data suggest basic psychophysiological differences between women and men which might extend to drug use tendencies.…”
Section: Gender Differencesmentioning
confidence: 89%
“…This study possessed the limitations of being performed at a single institution and in a small patient population. In addition, the gender imbalance of participants may affect the results [ 32 ]. The difference in exercise parameters between the three groups is another limitation of this retrospective data.…”
Section: Discussionmentioning
confidence: 99%